Pengaturan Pengangkatan Pejabat Negara Setingkat Menteri Sebelum dan Sesudah Perubahan UUD 1945 - Wiredarme - (Fakultas Hukum Universitas Mataram, 2015)
Executive authority to conduct presidential aide as a cabinet minister to prepare to run the government or the president is assisted by the ministers to continue the long-term plans, medium and short time. Based on the ideas which have been described in the above background it can be argued the issues as follows:. How does setting the appointment of a ministerial-level State officials before and after changes in 1945 and What is the procedure and requirements for the appointment of State level Ministry officials. as well as factors affecting the level of Minister of State appointments. From the results of the study as follows: Authority of the President in appointing a minister-level officials from sisitem presidential implementation as stipulated in the Constitution 45 in that it can be said before and after the process of changing the Constitution 45. In the first 45 before changing the Constitution by the president, as leader of the cabinet independently without being affected by elements related to the political overtones, while after the change of political situation is very influential with regard to the requirements and procedures in the appointment of a ministerial-level state officials. Requirements and procedures for the appointment of a ministerial-level officials before the change is highly dependent on the president but the phenomenon after the change of the Constitution a requirement that 45 appeared fit and propertest through a review and consideration of the House even though there are no normative requirements of this recruitment process is proven by the Attorney General and the Chairman and members of the Commission based on an Act to regulate both institutions and norms can be said of the void in the process of appointment of State level officials such as Attorney General and Minister for Leaders and members of the KPK. Factors affecting the authority of the President in the appointment of a ministerial-level state officials can be understood from two aspects: Internally is based on the needs of institutional aspects and the external cabinet. The conclusion of the recommendation is: It needs a legal setting and clear the form of laws and regulations that authorized the President to appoint state officials to ensure legal certainty as head of the cabinet on the basis of the Presidential system. In appointing the President of the ministerial-level State officials should prioritize the aspects of professionalism in accordance with the mandate of Law Number 43 Year 1999 and reduce the political overtones.